Factors contributing to change in the occupation of BRAC household heads - Mallick, Debdulal (BRAC, 2019)
This paper aims to explore the underlying reasons of BRAC household heads getting involved in farm and non-farm sectors, the nature and extent of change in their occupation between 1993 and 1996 and contribution of BRAC inputs in this change. Secondary analysis of IAS-I and lAS-II data collected in 1993 and 1996 respectively has been done for this paper. There had been only a marginal shift of occupation to the farm sector (3%) between 1993 and 1996. But actually there was a large inter group redistribution in occupational status as 33% of those engaged in farm activities in 1993 shifted to other sectors and 27% of those from non-farm sector switched to other sectors. Heads of the households with large family size and smaller amount of landholding switched to non-farm activities and so did those from villages with good infrastructure and marketing facilities. Household heads from villages with poor infrastructure and marketing facilities and with larger amount of landholding and receiving loan over Taka 5,000 were mainly engaged in farm activities. Such household heads who were previously engaged in the non-farm sector also switched to the farm sector.